Mitosis and Meiosis - Maiato, Helder; Schuh, Melina (Academic Press/Elsevier, 2018)
Front Cover -- Mitosis and Meiosis Part A -- Copyright -- Contents -- Contributors -- Preface -- Chapter 1: Assays for the spindle assembly checkpoint in cell culture -- 1. Introduction -- 2. Choice of Fluorescent Protein Tag -- 3. Choice of Microscope -- 4. Assays -- 5. Materials -- Acknowledgments -- References -- Chapter 2: Quantitative methods to measure aneuploidy and chromosomal instability -- 1. Introduction -- 2. Immunofluorescence Assay for Lagging Chromosomes in Anaphase -- 2.1. Instrumentation -- 2.2. Cell Culture Conditions -- 2.3. Antibodies -- 2.4. Immunofluorescence -- 2.5. Analysis -- 2.6. Alternative Method -- 3. Chromosome Missegregation Assay -- 3.1. Instrumentation -- 3.2. Cell Culture Conditions -- 3.3. FISH Probes -- 3.4. Preparation of Mitotic Cells -- 3.5. FISH Procedure -- 3.6. Analysis -- 3.7. Alternative Method -- 4. Aneuploid Cell Survival Assay -- 4.1. Instrumentation -- 4.2. Cell Culture Conditions -- 4.3. FISH Probes -- 4.4. Preparation of Interphase Cells -- 4.5. FISH Procedure -- 4.6. Analysis -- 4.7. Alternative Method -- 5. Concluding Remarks -- Acknowledgments -- References -- Chapter 3: Dissecting the role of the tubulin code in mitosis -- 1. Introduction -- 1.1. What Is the Tubulin Code? -- 1.2. Tubulin Isotypes -- 1.3. Tubulin PTMs -- 1.4. How Is the Tubulin Code Read? -- 2. Modulation of the Detyrosination/Tyrosination Cycle in Mammalian Cells -- 2.1. Cell Culture -- 2.2. Transient Overexpression of TTL -- 2.3. Depletion of TTL Using Small Interference RNAs (siRNAs) -- 2.4. Knockout of TTL Using CRISPR/Cas9 -- 2.4.1. Purchase oligos -- 2.4.2. Oligo annealing and cloning into viral transfer vectors -- 2.4.3. Transformation and selection -- 2.4.4. Lentivirus production -- 2.4.5. Transduction of lentivirus to target cells -- 2.4.6. Selection of knockout cells -- 2.5. Transient Overexpression of VASH1 and VASH2